Stoichiometric homeostasis in the food web of a chronically nutrient-rich stream - Feijoó, Claudia Silvina (2014)
The theory of ecological stoichiometry holds that heterotrophs are mostly homeostatic and exhibit less variation in body stoichiometry than do autotrophs. Most studies of stream foodweb stoichiometry have been done in low-nutrient environments. Little is known about foodweb stoichiometry in nutrient-rich streams, in which a higher level of stoichiometric homeostasis should be expected, mainly because imbalances between resources and consumers are low and nutrient availability may meet biotic requirements. We analyzed elemental content (C, N, P) and stoichiometric ratios (C:N, C:P, N:P) of basal resources, macroinvertebrates, and fishes in a nutrient-rich Pampean stream and compared these values to those from other studies. We manipulated P and N in a 1-y fertilization experiment to analyze biotic stoichiometric responses to additional nutrient input to this naturally enriched system. Soluble reactive P concentration in the treatment reach was doubled relative to the background concentration. Consumers had lower C:P and N:P than those in other lotic systems, whereas P content and C:P and N:P of basal resources were within the ranges observed for other systems. Most components of the trophic web were not affected by fertilization, and only epiphyton, fine benthic organic matter, and macroinvertebrate species (Palaemonetes argentinus and Pomacea canaliculata) changed their nutrient content or stoichiometric ratios. Imbalances in C:N and C:P occurred between primary consumers and their resources, particularly among macroinvertebrate collectors and detritivorous fishes feeding on FBOM. Most basal resources and consumers were strictly homeostatic for P content and the stoichiometric ratios, but a lower degree of homeostasis occurred in the epiphyton, P. canaliculata, and collectors feeding on epiphyton. A high degree of stoichiometric homeostasis exists across the various components of the food web in this nutrient rich stream, regardless of their trophic position.